PATHOMORPHOLOGICAL CHANGES OF THE ROOT CEMENTUM OF THE TEETH AGAINST THE BACKGROUND OF INFECTIOUS-INFLAMMATORY PROCESSES - Mazur, І.P.; Suprunovych, I.M.; Savosko, S.I.; Novoshytskyy, V.Ye. (World of Medicine and Biology, 2021)
Root cementum plays an important role in the regeneration of the periodontal complex. The purpose of the work was to study the pathomorphological changes of the root cementum of the teeth against the background of infectious-inflammatory processes in the periodontal tissues and mechanical influence on the root surface during periodontal treatment. The study material was 30 teeth with generalized periodontitis. According to the results of scanning electron microscopy, the surface of the teeth roots with generalized periodontitis had a heterogeneous appearance. Using area-specific Gracey curettes, the surface of the roots was smooth. Under the influence of the magnetostrictive ultrasonic scaler, the surface of the roots had a corrugated appearance. The surface of the roots after the application of magnetostrictive ultrasonic scaler and area-specific Gracey curettes was smooth with the presence of scales. According to the results of cementum morphometry of teeth longitudinal sections, a significant effect of area-specific Gracey curettes on the thickness of root cementum was established. Significant reduction in the thickness of root cementum in combination with increased masticatory load due to traumatic occlusion and low regenerative properties of cervical root cementum is a factor in the development of hyperesthesia and cervical lesions.
Keywords: periodontitis; cementum; microscopy; active periodontal treatment; regeneration